(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The theoretical foundations of state financial control, the activities of state financial control bodies, the essence of the concept of financial control, the organization of state financial control and its principles , the role of state financial control in developed countries, the main elements of state financial control have been studied.